Pengelolaan Limbah Medis Padat di RSUD Padangan Kabupaten Bojonegoro - Didik Wiyatno; Hamidah Rosidanti Susilatun (Lembaga Administrasi Negara, 2017)
The management of solid medical waste in RSUD Padangan Bojonegoro District is one of the efforts to create a clean and safe hospital condition from the source of infection for all officers, patients and environment in hospital. The management of solid medical waste in RSUD Padangan Bojonegoro District is viewed from the aspect of planning quite well, but there are still few problems such as the absence of global SOP for the management of hospital solid medical waste. For the organizing aspect is quite good, but the organizational structure in the Sanitation Unit has not been legalized its existence. Then the implementation aspect has gone well because it has been referring to the applicable regulation. While the supervision aspect has not run optimally because of the lack of regular supervision schedule conducted by Sanitarian. This study aims to determine the implementation of solid medical waste management in RSUD Padangan Bojonegoro District. Aspects studied in this study are: aspects of planning, organizational aspects, aspects of implementation, and aspects of supervision.Keywords: management, solid medical waste, hospital, RSUD Padangan, planning, organizing, implementation, supervision